Features of Vitamin Model Affecting Psychological Empowerment: Serial Mediation Role of Job Crafting and Work Engagement - Kumar, Gandhi Vasanth; B., Valarmathi (Prabandhan: Indian Journal of Management, 2022)
The current research aimed to investigate the association between the variables under the study, that is, ‘the vitamin model’ features of a job: job crafting, work engagement, and psychological empowerment. It also attempted to analyze the serial mediational role of the two causally linked mediators, that is, job crafting and work engagement with the job features of the vitamin model and psychological empowerment. By investigating these variables, we tried to explore how the employees redesigned the well-defined jobs to match their capabilities, which enhanced commitment to work and led to positive behavioral outcomes, such as empowerment, work meaningfulness, and improved performance. Primary data were collected from 453 knowledge workers in the information technology (IT) and information technology-enabled services (ITES) industry. Using SPSS software, the correlation method revealed significant positive correlations between the variables under study. PROCESS macro (Haynes, 2012) was applied in SPSS AMOS regression-based path coefficients and bootstrap confidence intervals at a 95% confidence level. As the bootstrap confidence intervals did not include zero, a significant mediational role of the serial mediators was observed between the relationship of features in the vitamin model and psychological empowerment [Estimate =.0761, 95% CI (.0257, .1902)]. So, it could be concluded that job crafting made the employees the mechanic of their vehicle (work), leading to work engagement, increased performance, and psychological well-being at the workplace.